2007
DOI: 10.1096/fasebj.21.5.a491-a
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in systemic glycocalyx volume in mice

Abstract: Experimental evidence suggests gender differences in atherogenic susceptibility. Given the role of the endothelial glycocalyx in vascular homeostasis, we compared in the present study systemic glycocalyx volumes in anesthetized female (F; n=6) and male (M; n=7) C57Bl/6 mice (~25 g body weigth (BW)). Systemic glycocalyx volume (Vg, in ml/kg BW) was determined from the difference in distribution volume (Vd, in ml/kg BW) of FITC‐labelled 70 kDa dextrans (D70), used as plasma tracer, and Texas Red‐labelled 40 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To evaluate the association between ISS and serum SDC-1, we performed multivariable regression analysis adjusted for covariates we defined a priori based on factors previously shown to be strongly associated with serum SDC-1 and ISS. For serum SDC-1, these were age ( 18 , 19 ), gender ( 20 , 21 ), previous treatment with transfusion and/or angiography at another hospital before being transported to our hospital ( 22 ). For ISS, these were: medication history of antiplatelet use and/or anticoagulant use ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the association between ISS and serum SDC-1, we performed multivariable regression analysis adjusted for covariates we defined a priori based on factors previously shown to be strongly associated with serum SDC-1 and ISS. For serum SDC-1, these were age ( 18 , 19 ), gender ( 20 , 21 ), previous treatment with transfusion and/or angiography at another hospital before being transported to our hospital ( 22 ). For ISS, these were: medication history of antiplatelet use and/or anticoagulant use ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, another study assessing the association of syndecan-4 levels with myocardial infarction, ischemic stroke, and all-cause mortality, found that syndecan-4 was associated with myocardial infarction only in women, suggesting a potential link between EG shedding and coronary artery disease in women [ 33 ]. Additionally, a murine model showed the presence of a gender difference in systemic glycocalyx volume, with female mice presenting a 50% reduction [ 34 ]. It is evident that sex affects EG both structurally and functionally, but data are still limited, and more studies are needed to evaluate the influence of sex on EG.…”
Section: Discussionmentioning
confidence: 99%
“…11 Earlier studies have reported that the factors that help ATIII in its functions are defective in females. [12][13][14] To our knowledge, the differential link between severe sepsis outcome and both arterial and venous ATIII levels in each gender is lacking. Therefore, the aim of the present study was to study the arterial and venous ATIII levels, in elderly males and females with severe sepsis, and their impact upon the patients' outcomes (septic shock, organ dysfunction as assessed by SOFA score and ICU mortality).…”
Section: Introductionmentioning
confidence: 99%